Integrating process optimization with energy-efficiency scheduling to save energy for paper mills. (1st September 2018) - Zeng, Zhiqiang; Hong, Mengna; Li, Jigeng; Man, Yi; Liu, Huanbin; Li, Zeeman; Zhang, Huanhuan
Highlights: A hybrid energy model is proposed for tissue paper mill. An energy efficiency scheduling model for tissue paper mill is developed. Proposes a two-level optimization method for tissue paper mill saving energy. The maximum energy cost saving ratio of dryer section is 12.53%. The maximum energy cost saving ratio of tissue paper mill is 9.03%. Abstract: With the surging energy price and environmental concerns, measures to improve energy efficiency have attracted increasing concerns of the manufacture sector, especially energy-intensive manufacturing industries such as tissue paper mills. Energy-efficiency scheduling, as a novel energy-efficient method, has attracted the attention of an increasing number of researchers in recent years. Drying process is the most energy-intensive production process in tissue paper mills, which has a great energy-saving potential. This paper aims to reduce the energy costs for the tissue paper mill, consisting of processing energy cost and set-up energy cost, through integrating drying process optimization with energy-efficient scheduling. First, the energy cost model and the scheduling model were built. Then, the energy cost of the drying process of every job in a given scheduling problem was optimized using particle swarm optimization (PSO). Afterwards, the energy cost was further optimized using energy-efficiency scheduling. In addition, a hybrid non-dominated sorting genetic algorithm II (NSGA-II) was utilized to solve the energy-efficiency scheduling problem. Finally, several real scheduling problems from a real tissue paper mill were addressed using the proposed approach to demonstrate its effectiveness in energy saving. The experiment result showed that there is a great energy-saving potential in the drying process, accounting for up to 12.53% of the total energy consumption. Moreover, the maximum energy saving ratio of the proposed approach could reach 9.03%. On the whole, the proposed approach can provide a new energy-saving method for tissue paper mills or other manufacturing industries.